GraphQL in Action - Buna, Samer (Manning Publications, 2021)
GraphQL in Action gives you the tools to get comfortable with the GraphQL language, build and optimize a data API service, and use it in a front-end client application. By working through set up, security, and error handling you'll learn to create a complete GraphQL server. You'll also unlock easy ways to incorporate GraphQL into your existing codebase so you can build simple, scalable data APIs.